A preliminary molecular study of the Iranian species of Calomyscus (Rodentia- Calomyscidae) using RFLP - B. Sahebjam; J. Darvish; E. Rastegar-Pouyani; R. Siahsarvie; S. Akbarirad (Iranian Journal of Animal Biosystematics, 2009)
The Calomyscidae is a small family of Rodentia that has recently been classified into 8 species in a single genus, Calomyscus. Currently 5 species are reported in Iran: C. elburzensis,، C. bailwardi، C. grandis ، C. urartensis and C. hotsoni. Species discrimination based on morphological characteristics is difficult, so this study re-evaluated the phylogenetic relationships and taxonomic status of the morphotypes within Calomyscus using PCRRFLP as a molecular marker. Forty-seven samples of Calomyscus spp from 9 geographically separated regions of Iran were analyzed. The cytochrome b gene was amplified by PCR, digested using 3 restriction enzymes, HinfI, HincII and HaeIII, and the patterns separated electrophoretically. Species of long tailed hamster were discriminated from one another. A phylogenetic analysis of the dataset produced well distinguished clades.